Grammar Through Gamified Storytelling: Empowering Learners Across Generations - Siti Khikmiyah khikmiyah; Ulfatus Sholihah (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study explores the integration of gamified storytelling into grammar instruction to empower EFL learners from various generational backgrounds in a university context. Grounded in the principles of active learning and digital engagement, the research employed a classroom action research (CAR) design over two cycles to investigate how gamified storytelling influences grammar mastery and learner motivation. Participants included the second and the fourth year English education students who engaged in interactive grammar lessons centered on narrative-based digital games. Data was collected through grammar tests, reflective journals, observations, and interviews. Findings indicated a significant improvement in students’ grammatical accuracy and increased learner autonomy, collaboration, and confidence. The gamified storytelling approach also helped bridge generational gaps in learning preferences by offering a flexible, creative, and student-centered learning environment. The implications suggest that combining grammar instruction with narrative-based games can foster a more inclusive and empowering EFL classroom, making grammar more relatable and enjoyable across age groups. This study contributes to the ongoing discussion on innovative grammar pedagogy and supports the use of technology-enhanced learning tools to promote engagement and equity.